REALITAS MASYARAKAT DALAM MEDIA - Ronda, Mirza (Universitas Prof. Dr. Moestopo (Beragama), 2006)
As a journalist, the objectivities and neutralist is a crucial thing to hold when they do their journalism tasks. Its seems an impossible thing to do. In fact, News or other journalisms products are not a reality. They just pieces of reality (Media Image) which is produced by an influenced and distorted product.